2014
DOI: 10.1186/s12870-014-0345-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of mitogen-activated protein kinase gene family in Gossypium raimondii and the function of their corresponding orthologs in tetraploid cultivated cotton

Abstract: BackgroundMitogen-activated protein kinase (MAPK) cascades play a crucial role in plant growth and development as well as biotic and abiotic stress responses. Knowledge about the MAPK gene family in cotton is limited, and systematic investigation of MAPK family proteins has not been reported.ResultsBy performing a bioinformatics homology search, we identified 28 putative MAPK genes in the Gossypium raimondii genome. These MAPK members were anchored onto 11 chromosomes in G. raimondii, with uneven distribution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 62 publications
3
35
0
Order By: Relevance
“…However, studies in crop species were still limited (Alam et al 2015;Chen et al 2015;Yan et al 2014;Zhang et al 2014b). Drought-imposed osmotic stress elicits ROS production (Krasensky and Jonak 2012).…”
Section: Discussionmentioning
confidence: 98%
“…However, studies in crop species were still limited (Alam et al 2015;Chen et al 2015;Yan et al 2014;Zhang et al 2014b). Drought-imposed osmotic stress elicits ROS production (Krasensky and Jonak 2012).…”
Section: Discussionmentioning
confidence: 98%
“…More recently, it was shown that BWMK1 is activated by fungal elicitors, hydrogen peroxide, salicylic acid, and jasmonic acid (Cheong et al, 2003). Other studies in cotton (Gossypium raimondii) showed that MPK9 (together with MPK13 and MPK25) confer resistance to Verticillium dahlia, which causes defoliation (Zhang et al, 2014). These studies provide evidence that these TDY MAPKs play a role in signaling to defense signaling.…”
Section: Identity Of Prmpk9-1 As a Tdy Mapkmentioning
confidence: 75%
“…This expression pattern is consistent with the known function of the p56-MAPK involvement in the SI response in mature pollen. We examined whether PrMPK9-1 was up-regulated after SI induction, as several MAPKs are up-regulated after stimulation, particularly stress treatments (Zhang et al, 2014). RT-PCR expression analysis of PrMPK9-1 revealed increased expression 10 min after SI induction in incompatible pollen specifically; compatible pollen challenged with the same PrsS did not show increased expression, nor did other control pollen samples ( Fig.…”
Section: Evidence Suggests That P56-mapk Is Encoded Bymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the conserved S/Txxxxx-S/T sequence and the D site, these motifs can be divided into Groups A, B, C and D (Kazuya et al 2002). The MAPK protein family is a promiscuous family of serine/threonine kinases that phosphorylates a variety of substrates, including transcription factors, protein kinases and cytoskeleton-related proteins (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%